1991
DOI: 10.1093/oxfordjournals.eurheartj.a059868
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular peak filling rate, heart failure and 1-year survival in patients with acute myocardial infarction

Abstract: Radionuclide left ventricular (LV) peak filling rate (PFR) was determined in 185 survivors of acute myocardial infarction (AMI) and expressed in units of (1) end-diastolic volume per second (EDV s-1). (2) stroke volume per second (SV s-1), or (3) actual millilitres of blood filled into the left ventricle per second (ml s-1). The purpose of the study was to assess the interrelationship between the three expressions of PFR, and to analyse their significance with regard to signs of congestive heart failure and 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…However, we have shown that different ectopic beat CIs result in different peripheral pulse amplitudes, with an average pulse amplitude increased by 4.8 times the normal sinus amplitude per second. This changing rate is comparable with the published normalized left ventricular peak filling rate around 4.2 EDV/s (Bacharach et al 1979, Gadsbøll et al 1991, Hui and Gibson 1983. Therefore, investigating peripheral pulse amplitude change with CI also provides a simple potential procedure for assessing the left ventricular peak filling rate non-invasively, and indicates when ectopic beats are likely to be associated with reduced cardiac output.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, we have shown that different ectopic beat CIs result in different peripheral pulse amplitudes, with an average pulse amplitude increased by 4.8 times the normal sinus amplitude per second. This changing rate is comparable with the published normalized left ventricular peak filling rate around 4.2 EDV/s (Bacharach et al 1979, Gadsbøll et al 1991, Hui and Gibson 1983. Therefore, investigating peripheral pulse amplitude change with CI also provides a simple potential procedure for assessing the left ventricular peak filling rate non-invasively, and indicates when ectopic beats are likely to be associated with reduced cardiac output.…”
Section: Discussionsupporting
confidence: 82%
“…It was reported that, in patients with coronary artery disease, the peak filling rate is decreased to 2.0 EDV/s (Rokey et al 1985) and 2.4 EDV/s (Betocchi et al 1993), measured from Doppler echocardiography and angiography respectively. Similarly, in patients with myocardial infarction and pulmonary arterial hypertension, the equivalent figures were reported to be 2.2 EDV/s (Gadsbøll et al 1991) and 2.7 EDV/s (Gan et al 2006) by angiography and MRI respectively. It has also been shown that premature ventricular contractions reduce stroke volume by an average of 71% compared with normal sinus beats, whereas the postextrasystolic beats increase stroke volume by only 18% over the sinus beats (Cohn and Kryda 1981).…”
Section: Introductionmentioning
confidence: 88%